A study of indigenous yaws amongst the Lango - Brown, John Scott (The University of Edinburgh, 1936)
(1) A clinical study of indigenous yaws, in an isolated Nilotic tribe is presented.

(2) An endeavour has been made to establish that yaws is common in this tribe, and that syphilis is rare. The past history of adjoining tribes is reviewed and it indicates that syphilis should become common amongst the Lango.

(3) With improving economic conditions, better standard of living and more treatment, yaws will disappear from Lango.

(4) The possibility of a fly vector is suggested.

(5) The cutaneous manifestations of yaws are discussed, and the clinical appearance of the lesions has been shown to be dependent upon the relative predominance of combinations of typical histological features.

(6) A classification of Common Framboesome, Annular Framboesom and Impetiginous Framboesome is shown to be adequate for the sango lesions.

(7) Unusual looking lesions have been encountered and are explained as being caused by reparative processes.

(8) The uniformity of the lesions in a given case is emphasised.

(9) Late skin lesions, such as Hyperkeratosis Plantaris and Palmaris have been referred to and their frequency commented on. The Lupoid type has been discussed at some length.

(10) The importance of bone lesions has received attention. The remarkable prevalence of dactylitis and periostitis in children during the acute stage of the eruption is introduced.

(11) The sociological effect of the disablement of parents by late yaws lesions has been pointed out.

(12) Treatment has been discussed, in general and also with particular relation to the results achieved in Lango. The importance of "Reservoir Cases" is mentioned.

(13) Immunology, particularly the immunological relationship between yaws and syphilis, has been studied, and the author offers his clinical observations in this connection. In his opinion yaws does not protect against venereal syphilis.

(14) Syphilis amongst Bantu Uganda tribes has been described briefly.

(15) The absence of visceral changes amongst the Lango, resembling those caused by syphilis is alluded to.